2019
DOI: 10.1186/s12955-018-1076-7
|View full text |Cite
|
Sign up to set email alerts
|

Rate of psychiatric disorders and associations with quality of life among community members following the Kaohsiung gas explosion: an 18-month cross-sectional follow-up study

Abstract: ObjectiveTo conduct a follow-up on the rate and related risk factors of probable disaster-related psychiatric disorders such as depressive disorder (major depressive episode, MDE), stress disorders, post-traumatic (posttraumatic stress disorder, PTSD), and the quality of life of the survivors of a fossil gas explosion in Taiwan 18 months after the event.MethodsA community-based survey of residents of a community that experienced a petrochemical gas explosion with cross-sectional assessments was conducted 18 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
4
18
0
Order By: Relevance
“…There were significant negative correlations between physical HRQOL scores and those of PCL-C. Higher scores of post-traumatic status in subjects were associated with greater odds of poor physical HRQOL after controlling for social demographic characteristics and earthquake-related losses. This finding was consistent with those in previous reports (21)(22)(23)(24). McMillan et al…”
Section: The Effects Of Pcl-c On Physical Healthsupporting
confidence: 94%
“…There were significant negative correlations between physical HRQOL scores and those of PCL-C. Higher scores of post-traumatic status in subjects were associated with greater odds of poor physical HRQOL after controlling for social demographic characteristics and earthquake-related losses. This finding was consistent with those in previous reports (21)(22)(23)(24). McMillan et al…”
Section: The Effects Of Pcl-c On Physical Healthsupporting
confidence: 94%
“…To our knowledge, studies on QOL across psychiatric disorders after traumatic experiences are very scarce in South Asia and in the Nepalese context in particular. The only study from Asia we found was from Taiwan following a major gas explosion in 2014; the study reported an association between PTSD and depression and various aspects of QOL, although the study population was not a clinical sample [62]. We came across a few studies from Asia linking QOL with psychiatric disorders in specific populations rather than trauma victims.…”
Section: Discussionmentioning
confidence: 99%
“…This variation is necessary due to type of accident; meanwhile, the high heterogeneity observed may be related to variability of study samples, since they are very different in terms of size, composition, and socioeconomic context. 6 , 12 , 30 Thus, caution is warranted with regard to inferences based on results of meta-analyses.…”
Section: Discussionmentioning
confidence: 99%